Protection of cyanobacterial carotenoids Raman signatures by Martian mineral analogues after high dose Gamma irradiation - Baqué, M.; Hanke, Franziska; Böttger, Ute; Leya, T.; Moeller, R.; de Vera, J. P. (Journal of Raman Spectroscopy, 2018)
The future robotic exploration missions to Mars—European Space Agency/Roscosmos ExoMars2020 and National Aeronautics and Space Administration Mars2020 rovers—will search for signs of extant or extinct life using, among other instruments, Raman spectrometers for the first time. The question remains whether organic biosignatures—such as pigments and cellular components—may be detected by this method. Evaluating their detection limit under simulated extraterrestrial conditions is therefore crucial for the success of future life detection missions. Ionizing radiation can be considered as the most deleterious factor for the long‐term preservation of potential biomarkers on Mars. Here, we report on the preservation potential of Raman signatures in the Antarctic strain CCCryo 231‐06 of the cyanobacterium Nostoc sp. after high doses of gamma irradiation. The carotenoids signals, a well‐ established biosignature model, dominate the Raman spectra at 532‐nm excitation wavelength due to resonance effects. But comparing their distribution and quantifying their preservation are still problematic in natural samples. To standardize the analyses, we successfully applied Raman mapping and signal‐to‐noise ratio masks to quantify the effects of irradiation. The typical in vivo Raman signatures of carotenoids could be detected after exposure to up to 56 kGy with significant deterioration in terms of signal coverage and signal‐to‐noise ratio. But they remained stable even after the highest dose of Gamma rays (117 kGy) tested in this study for colonies embedded in two different Martian mineral analogues. Data gathered during these ground‐based irradiation experiments contribute to interpret results from space experiments and will guide our search for life on Mars and other bodies of interest.